Growing Up with Capital Flows - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2002)
In a sample of 60 developing countries, we find evidence of a strong-almost one-to-one-relationship between capital inflows and domestic investment. However, this relationship has evolved over time. While growing financial integration with the rest of the world has increased access to foreign private capital, the relationship between foreign capital and domestic investment has weakened, reflecting changes in the composition of inflows, offsetting outflows, and increased foreign-currency reserve requirements. In contrast, better policies have not only brought in more capital but also, especially for foreign direct investment, have tended to strengthen the relationship between foreign capital and domestic investment.